Análise mecânica e química de placas pré-moldadas de concreto com adição de resíduos de borracha de pneus - Kroth, Leandro Agostinho (2012)
This work aims to analyze a building system that utilizes alternative material and residues of tire rubber in community housing. Primarily, this work shows a review of literature concerning housing, debit, environment, habitation projects in Brazil and recycling of used tires. Definitions, classification, types, models of technology and factors involving pré-fabricated comunits houses are also presented. In addition, characteristics of the Sistema Construtivo Bom-Plac are shown with detailed information of materials employed. Subsequently, measurements, probes and tests using concrete pre-cast slabs which with tire rubber are analyzed concerning moisture content, density, compressive strength and chemical analysis of the tire rubber. A better compressive strength reaching 14,38 MPa level was observed for mixture composition 1:2:0.5:2 (cement CP-V, sand, rubber and gravel number 1). To make sure that no heavy metals are released in the environment according to NBR 10006 of ABNT technical regulations chemical analysis were performed. Chemical analyses included tests evaluating water effect, solvability, pH, scanning electron microscopy, microbiology and water uses with and without sulfuric acid (H2SO4) and sodium hydroxide (NaOH). A brief report with experiences by the author are presented including the pré-fabricated type, habitation type, multi-functional septic tank and drainage are included in this thesis.